The Concept of Ta’liq Divorce Confirmation in the Terengganu Syariah Subordinate Court: A Case Study and Its Relationship with Authentic Hadiths (Contrarius Series: Law & Social Justice, 2026)
This research explores the implementation of ta’liq divorce confirmation applications at the Terengganu Syariah Subordinate Court, focusing on the main challenges faced by involved parties and proposing hadith-based solutions. Referring to Section 47 of the Islamic Family Law Enactment the research identifies key issues such as confusion among couples regarding the meaning and legal effect of ta’liq, procedural delays in case study and hearing, and inconsistencies in evidentiary requirements.The objective is to develop a conceptual model that provides a comprehensive and systematic guideline for husbands, wives, the Syariah Court, and the Religious Affairs Office to ensure that the ta’liq divorce confirmation process is implemented in an orderly and shariah-compliant manner. Using a qualitative case study approach, data were collected through the analysis of court files, statistical reports (2020–2024), and marriage records containing ta’liq clauses, complemented by semi-structured interviews and courtroom observations. Thematic analysis through content analysis was used to interpret the data. Findings indicate that most issues arise from limited legal awareness, weak documentation, and procedural misunderstandings. These can be mitigated through a unified framework emphasizing legal literacy, evidentiary responsibility, and verification grounded in hadith principles. The research thus contributes to developing a conceptual model that enhances judicial consistency, procedural efficiency, and societal understanding of ta’liq divorce verification in accordance with Islamic legal principles.